ANALISIS FAKTOR YANG MEMPENGARUHI KEBIJAKAN SALURAN DISTRIBUSI GUNA MEMENUHI TARGET PENJUALAN PADA PERUSAHAAN JAMU PT RUMPUT PATIMAH BANJARMASIN - Anisah, Hastin Umi; Hariyatie, Nira (Industrial and Systems Engineering Assessment Journal (INASEA), 2005)
The aim of this research is to find out the empirical evidence of the influence of factors that are the paying of agency, the number of potential consumer, volume of selling agency, sending time frequency, the number/ordering measurement, services which given by company, services which given by agency. Samples in this research are 19 selling agency of 19 selling agency in all of Indonesia areas. The examination of this research result in the founding that the gaining selling target of Rumput Patimah company is simultaneously influenced by some factors which already mentioned above.